The Field of In Between - Stein, Sarah Abrevaya (International Journal of Middle East Studies, 2014)
In the spring of 1902, Miryam bint Lalu Partush appealed to military representatives in Ghardaïa, in the Mzab Valley (a valley of five fortified oasis cities in the northern Algerian Sahara, six hundred kilometers south of Algiers), for the paperwork that would allow her to undertake a six-month pilgrimage to Jerusalem with her husband, the wealthy merchant Musa (Moshe) bin Ibrahim Partush. Miryam Partush was unusual in possessing the means for such a rare, costly voyage; but notwithstanding her class, Partush's legal status was typical of most Muslims and southern Algerian Jews in Algeria. She was not a citizen, nor did she hold official papers of any kind. When Miryam Partush appealed to the military authorities in Ghardaïa, then, she was appealing for many things: for the right to leave her native valley and travel to the port of Algiers; for the papers that would allow her to cross colonial boundaries; and for the documentation that would register her liminal legal identity. Authorizing her travel, Algeria's governor-general named Partush a “non-naturalized Jew from the Mzab.” Thus did Partush embark on her six-month journey with a negative legal identity: this Jewish woman was definable, in the eyes of the law, only by what she did not possess.
Keywords: Judaïsme -- Mzab